MODEL SUPERVISI INTEGRATIF UNTUK MENINGKATKAN PROFESIONALISME GURU DAN EFEKTIVITAS LEMBAGA PENDIDIKAN ISLAM - Riskiyah Pajriatul Amaliya; Raudhaturrahima; Nugraha, Mulyawan Safwandy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher professionalism and institutional effectiveness in Islamic schools require supervision that does not stop at administrative control. This study aims to explain the implementation of managerial, clinical, and collaborative supervision and to formulate an integrative supervision model at MIS Al-Jihad Padalarang. The study used a qualitative single-case study design. Data were collected in April 2026 through semi-structured interviews with a supervisor, the madrasah principal, and a teacher, as well as classroom observation and document analysis. Data were analysed through condensation, display, and conclusion drawing. Source and technique triangulation and an audit trail were used to strengthen credibility. The findings show that managerial supervision was conducted through annual scheduling, document review, coordination, and follow-up. Clinical supervision followed pre-observation, evidence-based classroom observation, and reflective post-observation. Collaborative supervision was carried out through teacher meetings, peer coaching, professional learning community activities, and lesson study. These practices strengthened administrative clarity, reflective teaching, confidence in using varied learning strategies, and collective responsibility. The study proposes a cyclical integrative model that connects managerial planning, clinical evidence, professional collaboration, and continuous follow-up, with amanah, ihsan, and hisbah as its ethical foundation. The model provides an operational framework for supervision in Islamic educational institutions.